Question and Answers Forum

All Questions      Topic List

None Questions

Previous in All Question      Next in All Question      

Previous in None      Next in None      

Question Number 123598 by aurpeyz last updated on 26/Nov/20

prove that ∫_0 ^a (√(a^2 −x^2 ))dx=((πa^2 )/4)

provethata0a2x2dx=πa24

Answered by Dwaipayan Shikari last updated on 26/Nov/20

∫_0 ^a (√(a^2 −x^2 )) dx        x=asinθ  ∫_0 ^(π/2) acosθ(√(a^2 −a^2 sin^2 θ)) dθ  =a^2 ∫_0 ^(π/2) cos^2 θ =(a^2 /2)∫_0 ^(π/2) 1+cos2θ dx  =((πa^2 )/4)+(a^2 /2)∫_0 ^(π/2) cos2θ =((πa^2 )/4)+(a^2 /4)[cos2θ]_0 ^(π/2) =((πa^2 )/4)

0aa2x2dxx=asinθ0π2acosθa2a2sin2θdθ=a20π2cos2θ=a220π21+cos2θdx=πa24+a220π2cos2θ=πa24+a24[cos2θ]0π2=πa24

Terms of Service

Privacy Policy

Contact: info@tinkutara.com